Factors Affecting Retention Intention Among Spa Therapists In Malaysia - Nor Fairuz Syazana Nor Fauzi; Raemah Abdullah Hashim, (Open University Malaysia (OUM), 2015)
The emergence of the spa industry had created opportunities for the industry to lead in the tourism sector, as discussed in the 2012 Global Spa and Wellness Summit in Bali. The wellness tourism has contributed $106 billion in the global industry and generated more revenue than any other sector in the tourism industry for example, medical tourism. In Malaysia, the spa industry has grown over 200% since 2002 and has the potential to continuously proliferate. Under the Malaysian Economic Transformation Program (ETP), among the 12 initiatives budgeted for tourism development, the spa industry development had caught the attention of private sectors. However, the industry is not without its problems. Besides competition from neighboring countries like Bali and Thailand, the spa industry in Malaysia has to also address issues regarding the lack of therapist expertise and service quality. The “lack of talent” in the spa industry is caused by high staff turnover when compared with the other services or other products in the tourism industry. Past studies had indicated that retention intention of employees is highly correlated to the overall job satisfaction. There are limited studies conducted in Malaysia in relation to spa therapist intention to remain in their job. Other factors that may influence retention are job related and lack of communication competencies. Personality is also an important factor where dissatisfaction may occur when it does not go well with the job. [ABSTRACT BY AUTHORS)